The Narrative Writing Handbook Development Supported by A Series of Pictures - Nugroho, Hartati, Dita Setyo (Elementary School Teacher, 2018)
AbstractThis study aimed to develop narrative writing guidebook asisted by series of pictures for the third grade students of Kalibanteng Kidul 02 SemarangÂ  Elementary School. This study used a Development Research approach (R&D) based on Sugiyono's theory that has been adapted to the study needs into seven stages of implementation . The results of this study indicated that: (1) the guidebook developed in accordance with the questionnaire of the needs of students and teachers ; (2) the guidebook was valid based on validation from material experts and media experts. A percentage of 95% was obtained with a very decent category of material experts and a percentage of 86.1% with a very decent category from media experts; (3) the percentage of teacher responses after using the guidebook classically was as much as 80.76% with a good criteria, while the percentage of students responses classically was 83.79% with a very good criterion; (4) the guidebook was effective for narrative writing lesson, the results of the analysis of the average difference in the t-test was 8.626 and the increase in the average gain was 0.43 with a medium criterion. The conclusion of this study was that the guidebook was suitable for learning activities